PENGGUNAAN AMOKSISILIN PADA FARINGITIS AKUT PEDIATRIK DI PELAYANAN RAWAT JALAN : TINJAUAN SISTEMATIS TENTANG PENGGUNAAN RASIONAL DAN HASIL KLINIS - Inge Maharani Ivo; Chairiati; Rahma Ziska (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to systematically examine the patterns of use, rationality, and clinical outcomes of amoxicillin therapy in pediatric acute pharyngitis in outpatient settings. A Systematic Literature Review (SLR) was conducted in accordance with the PRISMA guidelines. Literature searches were performed in PubMed, Scopus, Google Scholar, and Wiley Online Library for English-language articles published between 2018 and 2025. Article selection was guided by the PICO framework and strict inclusion criteria, resulting in 30 studies that were analyzed using thematic narrative synthesis aligned with the three research questions. The review findings indicate that amoxicillin and amoxicillin–clavulanate predominate in the outpatient management of pediatric pharyngitis, frequently prescribed without adequate confirmation of bacterial etiology. The rationality of use remains suboptimal, as evidenced by inappropriate indications, wide variability in dosing regimens, and treatment durations that often exceed clinical guideline recommendations. In terms of clinical outcomes, amoxicillin was shown to be effective in appropriately diagnosed streptococcal pharyngitis, with no additional benefit of broad-spectrum antibiotics in symptom resolution, but with a lower risk of adverse effects. These findings underscore the importance of strengthening rational antibiotic use practices to improve patient safety and reduce antimicrobial resistance in the pediatric population.